Issues Of Cultural Integration And Intercultural Communication In Audiovisual Translation - Bozorova Vasila Ilkhomovna (International Journal Of Literature And Languages, 2025)
Audiovisual translation (AVT) is a multidimensional practice that mediates between languages and cultures, enabling the global circulation of films, television programs, advertisements, and online media. Beyond linguistic transfer, AVT involves the careful negotiation of intercultural differences, national realities, and culturally sensitive content to ensure accessibility and audience comprehension. This essay explores the challenges of cultural coherence and intercultural communication in AVT, with a particular focus on English-Uzbek translation. It examines how translators employ neutralization of inappropriate elements, adaptation, and localization strategies to reconcile source and target cultural norms while maintaining communicative and stylistic effectiveness. The analysis highlights the interplay of linguistic, semiotic, and pragmatic factors, illustrating how audiovisual translators balance fidelity, readability, cultural relevance, and audience engagement. Ultimately, the study emphasizes that successful AVT requires a holistic, interdisciplinary approach that integrates translation theory, media studies, and cultural understanding to produce content that is both linguistically accurate and culturally resonant.